Pilot Study: A Prospective Placebo-control Trial Evaluating Topical Tranexamic Acid in Postmastectomy Breast Reconstruction - Nisha Parmeshwar, MD; Aileen Gozali, MM; Michael Choi, MS; Jacquelyn A. Knox, MD; Serena Bhaskerrao, BS; Catherine Lu Dugan, BS; Laura Esserman, MD; Merisa Piper, MD (Plastic and Reconstructive Surgery, Global Open)
Background:. Tranexamic acid (TXA) has been used off-label in many surgical fields to reduce bleeding and ecchymosis. However, given its theoretical thrombotic potential, it has not been widely used in breast cancer patients. The goal of this study was to prospectively evaluate the utility of topical TXA in postmastectomy breast reconstruction patients. Methods:. We performed a prospective trial of bilateral mastectomy patients after immediate implant-based reconstruction or flat closure, with each patient serving as her own internal control. After postmastectomy reconstruction and before skin closure, the right chest was treated with topical TXA solution and the left with normal saline. Demographics, surgical characteristics, and postoperative outcomes (hematoma, seroma, 24-h drain output, and total drain days) were compared. Results:. Twenty-three women (46 breasts) were enrolled. Tissue expanders were placed in 26 breasts (56.5%), implants in 12 breasts (26.1%), and flat closure was performed in 8 breasts (17.4%). There was no difference in infection rates, hematoma, seroma, or drain duration or output between the TXA and saline cohorts. The degree and extent of ecchymoses also did not differ postoperatively. Conclusions:. In this prospective trial uniquely designed for each patient to serve as their own control, we found no significant differences in key outcomes with the use of topical TXA solution after postmastectomy breast reconstruction. Continued studies evaluating topical TXA dosing and intravenous usage in a prospective fashion are necessary to determine its potential ongoing utility in postmastectomy reconstruction.